On Dr. Stockmann’s Parrhesia: Ibsen’s “An Enemy of the People” in the Light of Foucault - Haj’jari, Mohammad-Javad; Hooti, Noorbakhsh (Folia Scandinavica Posnaniensia, 2020)
An honest intellectual dutifully standing with truth against lies and treacheries of his society is a parrhesiastic figure in Foucault’s terminology. Foucault takes parrhesia as the fearless and frank speech regarding the truth of something or a situation before truth-mongering and public deception and he takes the parrhesiastic as the spokesperson for truth. In this light, Dr. Stockmann in Ibsen’s An Enemy of the People occupies a unique position within Ibsen’s political philosophy. Dutifully criticizing what the majority blindly take for granted from their liar leaders in the name of democracy, Dr. Stockmann fulfills the role of a parrhesiastic figure that stands against socio-political corruption. He enters a parrhesiastic game with both the majority and the officialdom to fulfill his democratic parrhesia as a truthful citizen before the duped community, while covertly preparing for his own philosophic parrhesia or self-care within the conformist community. However, his final failure lies in his confrontation with democracy itself, which wrongly gives the right of speaking even to the liars. This article thus aims at analyzing Ibsen’s play through a Foucauldian perspective regarding the concept of parrhesia and its relation to democracy. It is to reveal Ibsen’s satire on the fake ideology of democracy and highlight the necessity of humanity’s parrhesiastic self-care for the well-being of the self and the others.